Studi)Eksperimental)Karakteristik Laju Pemompaan Kapiler Pada Material Karbon)Bambu)Betung - Pangestu, Gusti Maulana; Ghurri, Ainul; Wijaksana, Hendra (Teknik Desain Mekanika; Vol 10 No 3 (2021): Juli 2021 : Teknik Desain Mekanika, 2021)
Abstract Cooling system is one of the necessities in everyday life. Especially in Indonesia with tropical climate. The cooling system is part of the air conditioning system, which is a system that is able to condition the air temperature or the room temperature lower than the ambient temperature. At Indonesia the average air temperature is 30oC- 35oC with an air humidity level of 70%- 80%. To get a comfortable air temperature certainly requires a large amount of electricity, with the use of air conditioning system, where the use of refrigerant in the air conditioning system can pollute the environment and also trigger the formation of a rise in global warming that continues to be a big problem. Because it has a poor environmental impact, a more energy-efficient and environmentally friendly cooling system is made. One the energy-efficient cooling systems is a direct evaporative cooling system that utilizes the sensible heat of the outside air to vaporize the layer of water contained in the wet pad material. This study aims to analyze the characteristics of capillary pumping rate in bamboo betung carbon material. As raw materials, bamboo could produce porous charcoall with a specific surface area and high porosity. Carbonization temperatures of 400ºC (TK 400), 500ºC (TK 500), 600ºC (TK 600), 700ºC are used (TK 700) and 800ºC (TK 800). The results of all tests showed that betung bamboo speciment which is carbonized at 500oC (TK 500) has the highest capillary pumping rate of 0.0478 g/s. Keywords: Bamboo betung, direct evaporative cooling, carbonization, capillary pumping rate, temperature